Catalytic transformation of non-edible oils to biofuels through hydrodeoxygenation using Mo-Ni/mesoporous alumina-silica catalysts. (15th February 2020) - Ramesh, Arumugam; Tamizhdurai, Perumal; Santhana Krishnan, Perumal; Kumar Ponnusamy, Vinoth; Sakthinathan, Subramanian; Shanthi, Kannan
Graphical abstract: Highlights: Synthesis of Mo-Ni over different mesoporous acid alumino-silicate catalysts. High oxygen removal efficiency of 85% was obtained with Mo-Ni/MAS (10) catalyst at 350 °C under 30 bar H2 pressure. High turnover frequency of 10.5 s −1 was found with high thermal stability. The absence of internal and external mass transfer resistance ascertained. Abstract: Bimetallic Mo-Ni was successfully impregnated on acidic mesoporous alumino-silicates supports. The acidic mesoporous alumino-silicates for instance, SBA-15, MAS, KIT-6, FSM-16 having Si/Al ratio = 10 were synthesized by post-grafting method. The effect of different mesoporous supports and active metals have been investigated through various characterization methods viz. XRD, H2 -TPR, NH3 -TPD, Raman, DR UV–Vis spectra, XPS spectra, TGA and SEM with EDAX and GPC results. The catalytic activity of present system is discussed in detail and compared with the previously reported studies. The prepared materials were analysed in a high-pressure reactor for HDO of non-edible oils (jatropha and watermelon oils) to biofuel productions by changing a number of reaction parameters for instance, reaction temperature (300 °C–375 °C), H2 pressure (10–40 bar), WHSV (0.5–2.0 h −1 ), and in addition Time on Stream (TOS). The nature of mesoporous supports and interaction between Mo-Ni active metals and acid supports were also investigated. This study demonstrates that Mo-Ni/MAS (10) catalyst have been successfully produced green fuel from non-edible oils (jatropha and watermelon oil) through the HDO pathway at 350 °C, WHSV 1.0 h −1, and 30 bar H2 pressure. The Mo-Ni/MAS (10) catalyst possesses unique surface properties such as high surface area 670 m 2  g −1, average pore diameter 4.3 nm, pore volume 0.81 cm 3  g −1, total acidity 2.07 mmol g −1, and considerable number of active sites 4.20 μmol g −1 . The specific reaction rates, as well as turn over frequency for Mo-Ni/MAS (10) catalyst, were found to be 4.31 × 10 −4  g s mol −1 and 10.5 s −1, which are considerably high. It has also been established that the reaction is unaffected by means of any resistance to mass transfer.